Impact frequency validation of head impact sensor technology for use in sport - Oeur, R. A.; Karton, C.; Hoshizaki, B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Head impact frequency has been identified as a contributing factor to long-term trauma experienced by the brain. A peak linear acceleration greater than 20g has been proposed as defining a single impact. The purpose of this study was to examine the accuracy of a single head impact sensor to identify 209 impacts under short (<7ms), intermediate (Ems), and long duration events (40ms) representative of falls onto hard surfaces, helmet to helmet collisions, and soccer ball to head. A Triax Smart Impact Monitor was outfitted on a Hybrid Ill headform. The headform was also instrumented with 9 accelerometers to record head acceleration. The headform and the head sensor were simultaneously impacted and corresponding outputs were compared. The head impact sensor was able to detect all short (5ms) and long duration impacts (40ms), however, for 15ms impacts, the sensor reported false negatives for 2 sites